Ability to receive compassion from others buffers the depressogenic effect of self-criticism: A cross-cultural multi-study analysis. (August 2016) - Hermanto, Nicola; Zuroff, David C.; Kopala-Sibley, Daniel C.; Kelly, Allison C.; Matos, Marcela; Gilbert, Paul; Koestner, Richard
Abstract: Self-criticism has been shown to be a vulnerability factor that can lead to and maintain depression. We examined the moderating effect of fear of receiving compassion from others on the positive association between self-criticism and depression. Self-report measures were administered to four separate samples (total N  = 701) varying in age (students and community adults) and cultural context (Canada, England, and Portugal). Two different measures of self-criticism and of depression were administered to investigate the generalizability of results. Self-criticism, depression, and fear of compassion from others were positively related to one another in all samples. As predicted, fear of compassion from others exerted a moderating effect on the relationship between self-criticism and depression. Low fear of compassion from others weakened the depressogenic effect of self-criticism, while high fear of compassion from others exacerbated the effect. Thus, a self-critic's ability to be open and responsive to care and support from others protected against depression. The aggregate moderating effect across the four studies was of medium size ( d  + = .53) and highly significant, indicating a robust phenomenon. Implications for working with self-critical depressed patients are discussed. Highlights: Fear of receiving compassion moderates the association between self-criticism and depression. High fear of compassion strengthens the depressogenic effect of self-criticism. Low fear of compassion weakens the depressogenic effect of self-criticism. Findings were replicated across 4 separate samples diverse in age and culture. A meta-analysis showed the aggregate effect was medium in size and robust.